2017
DOI: 10.1088/1742-6596/880/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Gravity and Cosmology: an intimate interplay

Abstract: Abstract. I will briefly discuss three cosmological models built upon three distinct quantum gravity proposals. I will first highlight the cosmological rôle of a vector field in the framework of a string/brane cosmological model. I will then present the resolution of the big bang singularity and the occurrence of an early era of accelerated expansion of a geometric origin, in the framework of group field theory condensate cosmology. I will then summarise results from an extended gravitational model based on no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…atoms of space, correspond to fundamental quanta which are created or annihilated by the field operators of GFT. 5 The GFT Fock space…”
Section: Group Field Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…atoms of space, correspond to fundamental quanta which are created or annihilated by the field operators of GFT. 5 The GFT Fock space…”
Section: Group Field Theorymentioning
confidence: 99%
“…In turn, this severe underdetermination of theory by experiment is a reason for the current presence of a plethora of contesting approaches to quantum gravity [4]. Against this backdrop, the cosmology of the very early Universe represents a unique window of opportunity out of this impasse [5]. For instance, it is naturally expected that traces of quantum gravity have left a fingerprint on the spectrum of the cosmic microwave background radiation, see e.g.…”
mentioning
confidence: 99%
“…This is a period of accelerated expansion in absence of an inflaton field and its associated ad hoc potential. A detailed study of the condition for inflation can be found in [12]; however, in [83] it is argued that the number of e-folds computed for the free theory -V = 0 in the action ( 6)-suggests that such a geometric inflation cannot last sufficiently long to accommodate observational data. This implies that GFT cosmology in absence of interactions between building blocks cannot replace the standard inflationary scenario.…”
Section: Discussion and Closing Remarksmentioning
confidence: 99%
“…According to [56] a real-valued condensate field has solutions avoiding the singularity and also growing exponentially after a bounce, if and only if the GFT energy is negative. A discussion on the possible values of the parameter space of the interacting potential can be found in [83], together with the stability properties of the evolving isotropic system, giving rise to effective continuous and homogeneous 3-geometries built from many smallest and almost at building blocks of quantum geometry.…”
Section: Discussion and Closing Remarksmentioning
confidence: 99%
“…Applied to cosmology, these ideas involve dramatic departures from the standard cosmological model [18], such as bouncing cosmological models, where the Universe undergoes a long, pre-big bang contracting phase which then bounces into the expanding Universe we observe today. Another possibility is an early era of accelerated expansion without the need for a special mechanism such as inflation.…”
mentioning
confidence: 99%